Managing security management in IT Call Centre as an outsource company to the multi national bank / Waidah Ismail - Ismail, Waidah (2004)
The meaning of security management is a deployment to provide a centralised, holistic view of corporate security and providing protection in new level. Security Management System can be defined as a management system used for establishing and maintaining a secure information environment. The relationship between the Security Management, IT Call Centre and Outsourced Company can benefit the Multi National Bank. The Literature Review has stated that a few companies that has outsourced their application and support to the local company in Malaysia. Further research was done via Internet, journals and newspapers are a good approach to obtain the latest information on the viruses attached, security management tools and a successful outsourced company. There are two methodologies used are questionnaire and research. The data is being analyse and validate from the survey. The process identifies the performance and enables management to learn and improve their performance of business processes by identifying the best practise in the company or industry. The problems faced in this independent study were the two sections on the questionnaire and further analysis. As for further analysis, the Multi National should think based on the BITS Framework before performing outsourcing. The recommendation was done based on the questionnaire showing that outsourcing is the best solution for security.